Phytochemical and Pharmacological Aspects of Psammosilene tunicoides W. C. Wu et. C. Y. Wu - Lian1, X.; Xie2, Q.H.; Duan1, A.H.; Chen1, Y.G. (Asian Journal of Chemistry, 2011)
Psammosilene tunicoides W. C. Wu et. C. Y. Wu (Caryophyllaceace) is an important medicinal plant which grows only in south-western part of China and has great medicinal value in traditional Chinese medicine to check bleeding, relieving pain and promoting blood circulation. It was also used as an important ingredient of some famous Chinese traditional medicine formulation. An attempt has been made to review the phytochemical and pharmacological work done on Psammosilene tunicoides.